Faktor yang Mempengaruhi Minat Investasi di Pasar Modal: Pendekatan Theory of Planned Behaviour (TPB) - Naila Rizki Salisa (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2020)
The investment intention is important to be explored because intention to invest in Indonesian capital market is still low. This study analyze the factors that influence investment intention by using Theory of Planned Behaviour (TPB). Through TPB, investment intention can be measured from explanatory variables which in turn will encourage actual behaviour. The variables used to predict investment intention are attitudes, subjective norms, perceived behavioural control, financial literacy, and risk perception. This study uses 161 respondents that were collected through a questionnaire. Data were analyzed with validity, reliability, and hypothesis testing using Structural Equation Modeling (SEM) through path analysis method. The results show that attitudes and subjective norms have no significant effect on investment intention. Meanwhile, perceived of behavioural control, financial literacy, and risk perception have a positive effect on investment intention in the Indonesian capital market. This results are expected to contribute for future research and provide advice to the government to design programs that can increase investment intention in the capital market.Keywords: Investment Intention, Theory of Planned Behaviour (TPB), Financial Literacy, Risk Perception